Lead Level Analysis in Roots and Leaves of Mangrove Plants Ceriops tagal and Rhizophora apiculata in Clungup Mangrove Conservation - Wibowo, Febri Arif Cahyo; Chanan, Mochamad; Pratama, Suci Intan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Indonesia is an archipelago with more water than land, which is battling water and land pollution. One form of pollution is lead which is commonly caused by battery waste, fishing boat activities, diesel waste. One solution is phytoremediation using hyperaccumulator plants such as mangroves. Mangroves can absorb heavy metals and maintain ecosystem stability. The dominant species in Clungup Mangrove Conservation are Ceriops tagal and Rhizophora apiculata. The objectives of this study were: 1) To determine the level of lead metal (Pb) pollution in mangrove sediments in the area. 2) To determine the levels of lead metal (Pb) in the roots and leaves of mangrove species Ceriops tagal and Rhizophora apiculata. 3) To determine the ability of lead metal (Pb) absorption in mangrove plants Rhizophora apiculata and Ceriops tagal. Research activities began on February 20th - May 31th, 2023. The research was conducted at Clungup Mangrove Conservation in Sumbermanjing Wetan District, Malang Regency. Lab tests were conducted at the Unism Integrated Laboratory and Halal Center. Lead test results in sediments in this area are classified as very low. Lead levels in the roots of Ceriops tagal were higher than Rhizophora apiculata. Pb levels in the leaves of Ceriops tagal were also higher than the leaves of Rhizophora apiculata. Bioconcentration Factor (BCF) values were higher than Rhizophora apiculata, but both were categorized as lead removal plants (BCF < 1). The Transfer Factor (TF) value showed a lower value for Ceriops tagal than Rhizophora apiculata, indicating that Rhizophora apiculata has better translocation ability. However, both are categorized as unstable plants (TF < 1). The results of the phytoremediation calculations showed that Ceriops tagal had superior absorption potential compared to Rhizophora apiculata.